Investigação de uma disciplina experimental optativa no contexto do PIBID UFG: uma leitura a partir das relações socioafetivas - Rocha, Layla Karoline Tito Alves (2015)
Socio-affetive relation are important for the construction of the teacher-student relationship and exhibit relevant contributions for the learning-teaching process. The Programa Institucional de Bolsa de Iniciação à Docência (PIBID) was our reserach field to try to understand those relationships built in the school context and what the implicatiions on the formation of those teacher are. Under the affection perspective presented by Henri Wallon we analyzed data colected from: an optional discipline of Experimental Science, scholarhsip awarded students that taught the course and the professor that supervised the school. Foloowing the assumptions of the Discursive Textual Analysis for the data analysis we obtained two categories, being The construction of the professor-student relationship that aims to understand the particularities of the relationship built between scholarship awarded students and the course's students, and The Initial Formation and Continued Formation, affective interactions on the formation of teachers that observerd the built relationship between the scholarship awarded student and the supervisor.